Effect of elevated temperatures on the shear-friction behaviour of concrete: Experimental and analytical study. (15th December 2020) - Ahmad, Subhan; Bhargava, Pradeep; Chourasia, Ajay; Usmani, Asif
Highlights: Shear-friction behaviour of concrete is investigated after elevated temperatures. Decrease in shear strength and increase in crack deformation was observed. Two methods for the prediction of residual shear strength were proposed. Abstract: Thirty-two uncracked shear-friction specimens were tested to investigate the effect of elevated temperatures on the shear-friction behaviour of concrete. Exposure temperature and the shear reinforcement were the principal variables. Specimens were exposed to high temperatures of 350 °C, 550 °C, and 750 °C in a programmable insulated closed electric furnace and were cooled down to room temperature before testing. Shear-friction specimens were also tested at the ambient temperature. Exposure of shear-friction specimens to high temperatures resulted in the decrease of shear strength of concrete. An increase in shear reinforcement reduced the loss in shear strength when specimens were subjected to high temperatures. The post-ultimate strength of the specimens was not reduced up to an exposure temperature of 550 °C. After experiencing high temperatures, crack slip and crack width at the shear plane increased significantly at all the load levels. Two simple approaches, modified Zia failure analysis and a simple calculation method (SCM) were also suggested for the prediction of shear strength of concrete after high temperatures. Modified Zia failure analysis provided precise estimates of shear strength for all the temperature levels. SCM was found to be precise for shear strength predictions up to an exposure temperature of 550 °C. For an exposure temperature of 750 °C, SCM was found to be unconservative by 20–30%.